Explaining the regional distribution of new economy firms: a count data analysis - Dirk Dohse; Andrea Schertler (Kiel Institute for World Economics (IfW), 2003)
Although there is a host of literature on the locational choice of traditional economy firms, relatively little is known about the locational needs and preferences of new economy firms. Therefore, the current paper provides an empirical analysis of the factors determining the regional distribution of new economy firms in Germany. Using a count data analysis, we find evidence that the number of firms listed in a particular region depends positively on the region's knowledge potential (as measured by the number of patents or by the number of R&D employees) as well as on the regional supply of venture capital.
Keywords: O30; C21; G24; R30; R58; 330; new economy firms; regional distribution; venture capital; knowledge potential; count data analysis; Unternehmensgründung; Standortwahl; Räumliche Verteilung; Wissen; Risikokapital; Schätzung; Deutschland